Pembelajaran berbasis masalah di pondok pensantren Miftahul Ulum dalam menigkatkan pembelajaran fikih - Nur Ali; Abuddin Nata; Ulil Amri Syafitri (SAP (Susunan Artikel Pendidikan), 2025)
Fiqh learning plays an important role in shaping students' understanding and religious practices. However, in reality, many students face difficulties in understanding Fiqh concepts in depth, especially in connecting them to everyday life problems. Teaching methods that are still conventional are often less effective in encouraging critical thinking and Islamic legal analysis skills. Therefore, innovation is needed in learning methods, such as the application of Problem-Based Learning (PBL) which emphasizes exploration and active problem solving. Problem-Based Learning (PBL) is an approach that emphasizes solving real problems as the first step in the learning process. This study aims to analyze the implementation of PBL in improving Fiqh learning at Miftahul Ulum Islamic Boarding School. The research method used is qualitative with a case study approach, involving observation, interviews, and document analysis. The results of the study indicate that the application of PBL in Fiqh learning at this Islamic boarding school is able to improve students' understanding of Fiqh concepts in more depth. Students become more active in discussing, analyzing Fiqh problems, and seeking solutions based on relevant arguments.